1990
DOI: 10.1093/ptj/70.5.302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Extremity Muscle Torque and Bone Mineral Density in Postmenopausal Women

Abstract: The purpose of this study was to examine the correlations between the torque of four extremity muscle groups and the bone mineral density (BMD) of the lumbar spine and hip in postmenopausal women. Fifty-six postmenopausal women (means age = 55.4 years, s = 7.1; means height = 162.6 cm, s = 6.4; means weight = 65.9 kg, s = 9.3) served as subjects. Bone mineral density was measured from the L2-L4 vertebral bodies, greater trochanter, femoral neck, and Ward's triangle using dual-photon absorptiometry. Hip abducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Our data show significant relations between the quadriceps muscle strength and femoral-lumbar bone density changes over one year of exercise. Zimmerman et al 27 and Bevier et al 28 have reported similar findings in postmenopausal women. It would seem that, if muscular strength is to be a determinant of bone density, the force of muscle contraction must impact on an anatomically related skeletal site or reflect actions of those muscles that do.…”
Section: Discussionmentioning
confidence: 61%
“…Our data show significant relations between the quadriceps muscle strength and femoral-lumbar bone density changes over one year of exercise. Zimmerman et al 27 and Bevier et al 28 have reported similar findings in postmenopausal women. It would seem that, if muscular strength is to be a determinant of bone density, the force of muscle contraction must impact on an anatomically related skeletal site or reflect actions of those muscles that do.…”
Section: Discussionmentioning
confidence: 61%
“…Bone density is positively associated with the strength of the anatomically related structures (Sinaki et al, 1986; Zimmermann et al, 1990). Furthermore, positive associations between bone mass and fat‐free mass (Aloia et al, 1995) and between BMD and muscular strength (Ryan et al, 1998) have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, femoral neck BMD is significantly correlated with hip abductor and flexor strength in postmenopausal women. 7,8 Finite element modeling studies have been widely used to examine bone remodeling, for example following total hip replacement, 9 with remodeling stimulus based on local strain energy density. However, there has been little examination of age-related differences in strains in the healthy intact femur, which may have implications for bone remodeling processes and maintenance of bone health in older adults.…”
Section: Introductionmentioning
confidence: 99%